Buchholzia coriacea seed extract attenuates mercury-induced cerebral and cerebellar oxidative neurotoxicity via NO signaling and suppression of oxidative stress, adenosine deaminase and acetylcholinesterase activities in rats - Simeon Egba; Ademola Famurewa; Lilian Omoruyi (Mashhad University of Medical Sciences, 2022)
Objective: Mercury (Hg) is a classic cumulative neurotoxicant implicated in neuronal deficit via oxidative damage and inflammatory responses. We sought to investigate whether Buccholzia coriacea seed methanol extract (BCSE) would modulate oxidative neurotoxicity induced by Hg in rats.Materials and Methods: Rats were orally treated with BCSE (200 or 400 mg/kg body weight of rat) for 28 days, while Hg was administered from day 15 to day 28. After sacrifice, antioxidant enzyme activities, reduced glutathione (GSH), nitric oxide (NO), malondialdehyde (MDA), and acetylcholinesterase (AchE) and adenine deaminase (ADA) activities were evaluated in the cerebrum and cerebellum of rats.Results: Mercury induced significant depressions in catalase (CAT) and glutathione peroxidase (GPx) activities and GSH levels, whereas levels of NO and activities of AchE and ADA markedly increased. The histopathology of the brain tissues confirmed these changes. In contrast, BCSE administration prominently modulated the brain NO production and reversed the Hg-induced biochemical alterations comparable to normal control.Conclusion: Methanol extract of B. coriacea seeds protects the cerebrum and cerebellum against Hg-induced brain damage via its antioxidant and NO modulatory actions.